Neuroradiology Classics - Wolpert, Samuel M. (American Journal of Neuroradiology, 1999)
Forward In our clinical practice and teachings of neuroradiology, we usually focus on the “here and now”, not the historical underpinnings. As Albert Lyons states in the introduction to his book on the history of medicine, “the student, practitioner, and public marvel at the contemporary medical scene, with its enlarged scientific understanding, remarkable diagnostic tools, effective therapeutic methods, and broadened attitudes toward the patient. Nevertheless, they are apt to view today's practices as either always having been there or contrarily as if they were unexpected bright meteors suddenly dropped from a dark sky” (Lyons AS, Petrucelli II RJ, eds. Medicine. An Illustrated History. New York: Harry N. Abrams, Inc.; 1987). Similarly, the basis behind the development of contemporary neuroradiologic practice often is forgotten, particularly by the young fellow or practitioner of the specialty.In this series, I will attempt to highlight and review those 10 neuroradiologic papers that could be considered to have the most significance for our current clinical practice. I stress the word clinical, not to impugn papers of major research interest, but to try to identify the relevant foundations of our day-to-day practice. In order to try to exclude a personal bias, I have chosen some of our more senior neuroradiologic graybeards to help me in my choice. Some of the reviews in this series will be written by them, other reviews by me. I am sure that we will have selected some contributions out of proportion to their real significance, and have ignored others that should have been chosen. For this we apologize. By design I have also chosen not to have articles published later than approximately 1993 in order to assess whether the published information has stood the test of at least 5 years of clinical application.I would like to thank O. Wayne Houser, Ralph Heinz, James Scatliffe, Norman Leeds, Michael S. Huckman, and Arthur Rosenbaum for their help in developing the list of the “10 best” and their contributions that will appear in subsequent issues of the AJNR.